PaDef (Persea americana var. drymifolia), a Plant Antimicrobial Peptide, Triggers Apoptosis, and Induces Global Epigenetic Modifications on Histone 3 in an Acute Lymphoid Leukemia Cell Line - Jiménez-Alcántar, Paola; López-Gómez, Rodolfo; López-Meza, Joel E.; Ochoa-Zarzosa, Alejandra (Frontiers in Molecular Biosciences, 2022)
In recent years, it has been recognized that epigenetic alterations play an important role in the development and maintenance of cancer, including leukemias. Furthermore, it is known that these alterations are involved in the emergence of resistance to conventional chemotherapeutics. Consequently, molecules with an anticancer activity whose activity is ruled by epigenetic modifications are attractive to search for new therapies against cancer. The plant antimicrobial peptides have been widely evaluated as molecules with anticancer activity; however, the analysis of the epigenetic regulation induced by these molecules associated with this activity is scarce and still is an unexplored field. In this work, we show that the PaDef defensin, a plant antimicrobial peptide from Mexican avocado fruit (Persea americana var. drymifolia) is cytotoxic for Jurkat cell line from acute lymphoid leukemia cells, through an apoptotic process. PaDef inhibited cell viability in a concentration-dependent manner, with an IC50=47.3 µM. Treatment of Jurkat cells with PaDef (IC50) induced cell death by apoptosis dependent on caspases 8 and 9; besides, it was related to an increase in the production of reactive oxygen species and the loss of mitochondrial membrane potential. Interestingly, the inhibition of caspase activation by inhibitors of caspases 8 and 9 does not revert the reduction in viability, suggesting that other mechanisms, in addition to caspase activity, could be participating in the PaDef cytotoxic effect. Also, the modifications in the histone 3 tails induced by PaDef in Jurkat cells were evaluated, specifically acetylation and methylation. PaDef increased global histone 3 acetylation and lysine 9 specific marks (2-fold and up to 4-fold, respectively). These effects correlated with the reduction of the Histone Deacetylase activity (HDAC, 50%). Concerning methylation marks, PaDef treatment increased lysine 9 di- and tri-methylation tags (2-fold in both cases). The epigenetic modulation induced by PaDef on Jurkat cells could be related to the chromatin compaction-decompaction promoting gene expression or repression; however, further studies are necessary to correlate these marks with the transcription of specific genes. Therefore, the study of new molecules that may have anticancer activity through epigenetic modulation is interesting.